2005
DOI: 10.1080/08035250410025294
|View full text |Cite
|
Sign up to set email alerts
|

Childhood idiopathic thrombocytopenic purpura in the Nordic countries: Epidemiology and predictors of chronic disease

Abstract: In the Nordic countries, ITP mainly affects children aged 0-7 y, with a winter bulk of postinfectious cases superimposed on a steady occurrence of non-infectious cases. Clinically, it may be useful to distinguish between children with sudden versus insidious onset of symptoms rather than between different age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
105
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 28 publications
17
105
1
5
Order By: Relevance
“…Zeller and colleagues showed that most childhood ITP cases occurred during winter months (11). In another study performed by Hafiz et al (12), childhood ITP was mostly diagnosed during the summer and at least in the winter.…”
Section: Discussionmentioning
confidence: 96%
“…Zeller and colleagues showed that most childhood ITP cases occurred during winter months (11). In another study performed by Hafiz et al (12), childhood ITP was mostly diagnosed during the summer and at least in the winter.…”
Section: Discussionmentioning
confidence: 96%
“…1 In childhood, ITP is characterized by a typical history of acute development of purpura and bruising in an otherwise healthy child, caused by development of platelet autoantibodies, with an incidence of ;5 in 100 000 children. 2 Most children with newly diagnosed ITP will not suffer from serious bleeding and will recover within 12 months. In ;60% of ITP, there is a history of a prior infection.…”
Section: Introductionmentioning
confidence: 99%
“…In ;60% of ITP, there is a history of a prior infection. [1][2][3] FNAIT is a potentially destructive disease in pregnancies, with intracerebral hemorrhage (ICH) of the fetus or neonate as the most feared complication, resulting in perinatal death in 1% to 7% or in severe neurological impairments in 14% to 26% of affected pregnancies. [4][5][6][7] FNAIT is caused by maternal IgG platelet alloantibodies, in whites mainly directed against human platelet antigen (HPA)-1a (85%), that cross the placenta and destroy the platelets of the fetus or newborn.…”
mentioning
confidence: 99%
“…1,2,4,5 In children, IVIG given alone may result in a greater acute rise in platelet count than seen with steroids. Platelet transfusion is reserved for severe hemorrhage.…”
mentioning
confidence: 99%
“…Platelet transfusion is reserved for severe hemorrhage. [1][2][3][4][5] There are other potential causes of Figure 1. Scattered petechiae over the patient's face, neck, and upper torso (left) and appearance of the patient's lower extremities with diffuse petechiae, purpura, and regions of ecchymoses (right).…”
mentioning
confidence: 99%